Analysis of Traffic Characteristics on Pasar Kapasan Street, Surabaya, in Front of Kapasan Market, Surabaya - Wahyu Ali; Hanie TekiTjendani; Nurani Hartatik (Jurnal Ilmiah Multidisiplin, 2025)
Surabaya is a metropolitan city with many major roads. Roads are essential infrastructures that are greatly needed. A roadway is one of the most important transportation facilities, as it connects one place to another. Therefore, the condition of a road segment greatly affects road performance. Pavement on roadways helps maintain the road in good and stable condition so that road users feel safe and comfortable when driving. However, various problems often occur, such as traffic congestion or vehicle buildup on certain road segments. One of the contributing factors is on-street parking. On-street parking along Kapasan Street, Surabaya, frequently causes congestion, preventing the road segment from functioning as intended. Kapasan Street in Surabaya is the object of this study. The purpose of this research is to analyze the traffic characteristics and the degree of saturation caused by on-street parking on Kapasan Street, Surabaya. The methods used include field surveys and direct observation. The study was carried out for one week with predetermined time intervals. Four surveyors were involved in data collection, and a traffic counter application was used to gather the data. The analysis results show that the highest traffic volume occurred on Monday, with a value of 13,387.95 pcu/hour. Traffic speed peaked on Sunday at 683.49 km/hour, the highest density occurred on Thursday with a value of 997 vehicles/hour, and the highest degree of saturation occurred on Friday with a value of 0.76. The conclusion from this analysis is that on-street parking significantly affects traffic characteristics.